Matematyka
polonista123
2018-01-01 13:56:09
Rozwiąż układ równań metodą podstawiania. 3(2x-1) + 4 (y-2) =9 2(5x-1) + 3y = 5(3x+y) + 2
Odpowiedź
ania99999
2018-01-01 17:24:36

3(2x-1) + 4 (y-2) =9  2(5x-1) + 3y = 5(3x+y) + 2 6x - 3 + 4y- 8 = 9 10x - 2 + 3y = 15x + 5y + 2 6x + 4y - 11= 9 10x + 3y - 2= 15x +5y + 2 6x + 4y = 9 + 11 10x +3y - 15x - 5y = 2 + 2 6x + 4y = 20  /:2 -5x -2y= 4  /*(-1) 3x + 2y = 10 5x +2y = -4 2y = 10 -3x 5x + 2y = - 4 2y = 10- 3x 5x + (10 -3x) = -4 2y = 10 - 3x 5x + 10 - 3x = - 4 2y = 10 - 3x 5x -3x = - 4 - 10 2y = 10 - 3x 2x= - 14 2y = 10 - 3x x = - 14 : 2 2y = 10 - 3x x= - 7 2y = 10 - 3*(-7) x= - 7 2y = 10 - (-21) x= - 7 2y = 10 + 21 x = - 7 2y = 31 x= - 7 y = 31 : 2 x= - 7 y= 15,5 x= - 7 spr. 3(2x-1) + 4 (y-2) =9  L = 3(2x-1) + 4 (y-2) = 3(2*(-7) -1) +4(15,5 -2) = 3(-14 -1) + 4*13,5= 3*(-15) +54 = - 45 + 54= 9 P= 9 9=9 L=P 

Dodaj swoją odpowiedź